2016
DOI: 10.1016/j.stemcr.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Hematopoietic Engraftment after in Utero Transplantation through Vascular Niche Manipulation

Abstract: SummaryIn utero hematopoietic stem/progenitor cell transplantation (IUHSCT) has only been fully successful in the treatment of congenital immunodeficiency diseases. Using sheep as a large animal model of IUHSCT, we demonstrate that administration of CD146+CXCL12+VEGFR2+ or CD146+CXCL12+VEGFR2− cells prior to, or in combination with, hematopoietic stem/progenitor cells (HSC), results in robust CXCL12 production within the fetal marrow environment, and significantly increases the levels of hematopoietic engraftm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Mokhtari et al . demonstrated that transplanted human CD146 + BM cells could increase CXCL-12 production in the large animal fetal recipient, triggering HSC reconstitution [ 85 ]. That process could mimic a physiological one.…”
Section: Bm Perivascular Cell Stemness and Regenerative Potentialmentioning
confidence: 99%
“…Mokhtari et al . demonstrated that transplanted human CD146 + BM cells could increase CXCL-12 production in the large animal fetal recipient, triggering HSC reconstitution [ 85 ]. That process could mimic a physiological one.…”
Section: Bm Perivascular Cell Stemness and Regenerative Potentialmentioning
confidence: 99%
“…In addition, the high proliferative potential and rapid doubling times ensure that clinically relevant numbers of UCT-derived cells, i.e., a total of 10 7 (clinically employed dose: 10 7 –10 8 cells/kg fetal weight) could quickly be obtained. In similarity to AF-MSC, in utero transplantation of MSC and EPC results in long term engraftment in treated animals without any adverse effects ( Colletti et al, 2009 ; Wood et al, 2012 ; Mokhtari et al, 2016 ). Thus, these qualities combine to make UCT-MSC and UCT-EPC particularly attractive candidates for cellular delivery vehicles for FVIII, and likely other gene products as well.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (Lonza, Walkersville, MD, United States) and HHSEC (Science Cell Research Laboratories, Carlsbad, CA, United States) were purchased and expanded in EGM-2 according to manufacturer’s instructions, as previously described in detail ( Sanada et al, 2013 ; Mokhtari et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, co-transplantation with stroma can selectively influence the expression of homing receptors and ultimately improve engraftment, as hematopoietic activity increases considerably after stromal establishment (Flake and Zanjani, 1999). Indeed, co-transplanted stromal cells expressing CD146, CXCL12, and VEGF led to improved engraftment in sheep (Mokhtari et al, 2016).…”
Section: Host Competitionmentioning
confidence: 99%